2018
DOI: 10.1111/bjh.15513
|View full text |Cite
|
Sign up to set email alerts
|

Bendamustine and rituximab in elderly patients with low‐tumour burden follicular lymphoma. Results of the LYSA phase II BRIEF study

Abstract: The treatment of low-tumour burden follicular lymphoma (LTBFL) remains a challenge. Rituximab-based strategies may be improved by adding chemotherapy. This Lymphoma Study Association multicentre phase II study assessed rituximab and bendamustine in 63 patients with untreated LTBFL who were aged over 60 years old and had a follicular lymphoma International Prognostic Index (FLIPI) score ≥2. Induction comprised 4 weekly cycles of rituximab 375 mg/m intravenously combined with 2 cycles of bendamustine 90 mg/m day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…These studies provide support for BR as the primary therapy for FL. However a Medicare database review did demonstrate unacceptable treatment‐related mortality with bendamustine in low tumor burden patients over age 60 70 . Bendamustine should be used with caution in elderly patients, particularly those with co‐morbidities, and reduced doses should be used as necessary.…”
Section: Initial Treatment Of Advanced‐stage Diseasementioning
confidence: 99%
“…These studies provide support for BR as the primary therapy for FL. However a Medicare database review did demonstrate unacceptable treatment‐related mortality with bendamustine in low tumor burden patients over age 60 70 . Bendamustine should be used with caution in elderly patients, particularly those with co‐morbidities, and reduced doses should be used as necessary.…”
Section: Initial Treatment Of Advanced‐stage Diseasementioning
confidence: 99%
“…These studies provide support for BR as the primary therapy for FL. However a Medicare database review did demonstrate unacceptable treatment related mortality with bendamustine in low tumor burden patients over age 60 …”
Section: Initial Treatment Of Advanced Stage Diseasementioning
confidence: 99%
“…This trial showed that grade 3–5 infections occurred more frequently in patients treated with bendamustine, caused by a marked reduction in CD3+ and CD3+ CD4+ T cells during induction in both antibody arms, with prolonged recovery during and after maintenance. The uncertain safety of rituximab maintenance after bendamustine in elderly patients is also highlighted by the study of Gyant et al that was prematurely ended because of a high frequency of haematological toxicity and serious AEs during the maintenance phase and follow‐up 29 . In our study, the very low late infection rate may suggest a benefit of the reduction of the number of bendamustine courses and the absence of maintenance.…”
Section: Discussionmentioning
confidence: 52%
“…The uncertain safety of rituximab maintenance after bendamustine in elderly patients is also highlighted by the study of Gyant et al that was prematurely ended because of a high frequency of haematological toxicity and serious AEs during the maintenance phase and follow-up. 29 In our study, the very low late infection rate may suggest a benefit of the reduction of the number of bendamustine courses and the absence of maintenance.…”
Section: Discussionmentioning
confidence: 52%